The bioactive peptides salusins and apelin-36 are produced in human arterial and venous tissues and the changes of their levels during cardiopulmonary bypass - Aydin, Suna; Eren, Mehmet Nesimi; Aydin, Suleyman; Ozercan, Ibrahim Hanefi; Dagli, Adile Ferda (Elsevier Science Inc, 2012)
This study aimed to examine the effects of CPB on salusin-alpha, salusin-beta and apelin-36 bioactive peptides in people who are planned to undergo coronary artery bypass graft (CABG) operation due to coronary artery disease and to explore whether these peptides are produced in human aortic, saphenous and arterial tissues. The study included age and BMI matched 15 patients who underwent CABG operation by CPB. In order to determine salusin-alpha, salusin-beta and apelin-36 levels, venous blood samples were collected before induction of anesthesia (T1), before CPB (T2), 5 min before the removal of cross-clamp (T3), 5 min after the removal of cross-clamp (14), upon arrival in the intensive care (15), at postoperative 24th hour (16) and 72nd hour (T7). Salusin and apelin expressions of the tissues were shown by immunohistochemical method. Peptide amounts of sera and tissues were measured using ELISA. Salusins production by vessels occurs in fibroblast cells of the media in the aorta and smooth muscle cells of the media in the LIMA and saphena. Apelin is produced by endothelial cells of the intima and fibroblast cells of the media in the aorta and by smooth muscle cells of the media in the LIMA and saphena. Changes in the levels of salusin-beta and apelin-36 were significant during CPB. Salusin-alpha, salusin-beta and apelin-36 are locally synthesized in the arteries and veins. Salusins and apelin-36 might be important markers in the CPB, and also that salusin-beta was more specific in comparison to salusin-alpha. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Salusin-alpha; Salusin-beta; Apelin-36; Bioactive peptides; Coronary artery bypass; LIMA; Saphena